Periurethral abscess in pregnancy: a rare incidence - Kalapala, Adarsha; Byyarapu, Vijaya Bharathi; Ramadugu, Amulya; V., Vishnuvardhan Reddy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Periurethral abscess in pregnancy has a rare incidence. The article showcases 2 case report of periurethral abscess in 3rd trimester of pregnancy, presenting symptoms, clinical features, imaging modalities for confirmation of the abscess and prompt management of the abscess with description of various modes of approach in dealing with such abscess.